Analyses and design procedure of a new physical model for debris flows: results of numerical simulations by means of laboratory tests - Moraci, Nicola; Pisano, Marilene; Mandaglio, Maria Clorinda; Gioffrè, Domenico; Pastor, Manuel; Leonardi, Giovanni (Italian journal of engineering geology and environment, 2015)
Debris flows are landslides that may involve large volumes of material and, due to their rapid propagation, they may be potentially dangerous for human lives and lifelines. In this paper, numerical simulations carried out for designing an instrumented large-size physical model are shown. In particular, a parametric analysis has been performed in order to reproduce, with the flume tests, the debris flow velocities observed during real events. Since the used computational code requires setting the specific rheological laws, several preliminary experimental tests have also been carried out, with the aim to find the rheological behaviour of the debris flow material.